A review of fossil scorpion higher systematics - Dunlop, Jason A.; Garwood, Russell J. (PeerJ, 2024)
Scorpions (Arachnida: Scorpiones) are a diverse and widespread arachnid order with a rich and deep fossil record. Here we review the, sometimes complex, historical development of fossil scorpion higher classification. We present a chronological account of family and genus names, together with an overview of higher taxa as potential clade names. In 1884 Thorell & Lindström divided scorpions based on whether the legs were short and pointed (Apoxypoda) or ended in paired claws (Dionychopoda). Pocock in 1911 used the morphology of the ventral mesosomal sclerites, which could either be bilobed (Lobosterni) or of a modern configuration (Orthosterni). Petrunkevitch in 1949 attached importance to a putative first opisthosomal tergite being present (Protoscorpionina) or absent (Euscorpionina). Kjellesvig-Waering in 1986 recognised four major groups (Holosternina, Meristosternina, Lobosternina and Bilobosternina) based on the shape of the ventral mesosomal sclerites. The Stockwell/Jeram schemes from the 1980s and 1990s proposed a cladistic progression from early branching lineages, for which the names Protoscorpiones and Palaeoscorpiones were used, towards Scorpiones sensu stricto defined by the presence of book lungs and coxapophyses. Scorpiones was further divided into Mesoscorpionina and Neoscorpionina. Neoscorpions were characterised by a reduced number of lateral eye lenses and comprise the paleosterns, with marginal lung spiracles, and orthosterns with spiracles in the middle of the sternite. We briefly discuss the merits of these alternatives and present a summary of the current higher classification of scorpions. Forty-three extinct family groups are currently recognised, and of the 24 living families seven have fossil representatives. Including incertae sedis taxa, there are 76 extinct genera and five extant genera with fossil representatives. Both modern parvorders, Buthida and Iurida, were potentially present in the Triassic. Buthidae, Chaerilidae, Chactidae and perhaps Hormuridae have been reported from the Cretaceous. Euscorpiidae are known from the Palaeogene and Scorpionidae has potential (but unconfirmed) records from the Neogene. Given the complexity of this history and the present taxonomy of the group, we hope this contribution provides a first step towards simplifying fossil scorpion systematics.
Keywords: Scorpiones; Fossils; Higher classification; Families; Arachnids; Arachnopulmonata